The influence of customer complaint behavior and brand image on the repurchase intention of j&t express services (study on expedition service users in Medan City) - Sibarani, Yunanda; Siregar, Onan Marakali (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
Expedition Services is a service product that is a basic need for people who want to buy or send goods in different places, one of which is the marketplace. The high interest in the use of expedition services makes the expedition business compete fiercely and attract the attention of consumers and continue to innovate. This study aims to determine the influence of customer complaint behavior and brand image on repurchase intention in Medan City. The influence between customer complaint behavior and brand image will be analyzed partially and simultaneously on repurchase intention. The form of research used in this study is quantitative research with an associative approach. Sampling was carried out purposive sampling using 100 respondents as a sample.